The magic show - Geatches, Hazel (United Kingdom : Aardman animations limited, 2021)
Timmy and Osbourne do a magic show.
"The Magic Show" likely follows Timmy and his friends as they put on or experience a magic show. It probably involves simple magic tricks, and the fun and excitement associated with such performances, geared towards beginner readers of English. Location: 2A
Keywords: Magic book